Effect of Blumea balsamifera extract on the morphology and nucleation of calcium oxalate crystals - Montealegre, Charlimagne M. (College of Engineering, University of the Philippines Diliman, 2015)
Kidney stone formation is a prevalent health problem facing mankind. Its main component is Calcium oxalate monohydrate (COM). Modern treatments such as shockwave lithotripsy, surgery and western medicine exist but few studies quantify the naturopathic effect of herbal medicines such as Blumea balsamifera or Sambong. The effect of B. balsamifera extract on the morphology and nucleation behavior of calcium oxalate crystals was studied using light microscopy and induction time analysis. The presence of B. balsamifera extract in the crystallization solution dramatically reduced the formation of COM crystals and promoted Calcium oxalate dihydrate (COD) crystal formation from a COM fraction of 0.9932 ± 0.0122 to 0.1158 ± 0.1287 and 0.08417 ± 0.0928 upon addition of 0.5 mg/mL and 1.0 mg/mL of extract. A dramatic change in crystal size was also observed with the 38-77% reduction in Area mean Feret diameter. Induction time studies was performed to calculate the surface free energy. Without the extract, a surface free energy of 21.8 mJ/m2 was calculated. This differs by 77.7% from the predicted surface energy by Mersmann corerlation. It was found that an increasing extract concentration decrease the surface energy to 19.48 and 17.21 mJ/m2 at 0.5 and 1.0 mg/ML of extract, respectively. This corresponds to a decrease in critical nuclei size, critical Gibbs Free energy of formation, and crystal size. The study showed that the extract favored the formation of smaller COD crystals instead of COM due to an increased nucleation rate. A possible reason for this is the change in calcium ion speciation due to its interaction with the phytochemicals in the extrac